STUDI PERBANDINGAN METODE TRANSFORMASI DNA MENGGUNAKAN VEKTOR Agrobacterium tumefaciens PADA TANAMAN TEBU (Sacharum hybrid) - Sri Setyati; Purnama Oktaviandari; Muhammad Hazmi; Bambang Sugiharto (The East Java Biological Society, 2007)
In order to compare transient expression of gus gene driven by CaMV 35S and rice ubiquitin RUBQ2 promoters, a DNA transformation was conducted using embryogenic callus and suspension cultures of sugarcane. The transient gus expression was observed by histochemical staining method. The histochemical observation of GUS activity after co-cultivation showed that RUBQ2 promoter produced high level of clear blue spots both in embryogenic callus and suspension cultures, while the CaMV35S promoter was not detected. The suspension cultures slightly increased transient gus gene expression compared to embryogenic callus. However, the histochemical analysis of regenerated putative transformant plants after 5 successive cycles on the selection medium showed no blue spots of gus gene expression. PCR amplification of DNA for CaMV35 or nptII in putative transformant plants confirmed that there was no integration of the transformed gene in the genome DNA. The results suggested a possibility of somaclonal variation with callus propagation, thus did not produce transformed plants. To avoid the somaclonal variation, the transformation was conducted using in vitro plants and multiple shoots without intervening callus phase. Histochemical observation of infected materials after co-cultivation showed that almost all of the infected materials partially exhibited blue color in the basal region. In case of in vitro plants, they rapidly grow and multiplied in the selection medium, thus the method provided an excellent system for the transformation in sugarcane. The results suggest that in vitro plants as well as multiple shoots need further investigation to be used as target tissues for Agrobacteriummediated transformation in sugarcane.